Primary culture and mRNA analysis of human ovarian cells - Dunfield Lesley D.; Shepherd Trevor G.; Nachtigal Mark W. (Biological Procedures Online, 2002)
Established cell lines are invaluable for studying cell and molecular biological questions. A variety of human ovarian cancer (OC) cell lines exist, however, most have acquired significant genetic alterations from their cells of origin, including deletion of important cell cycle regulatory genes. In order to analyze signaling events related to cell cycle control in human OC, we have modified existing protocols for isolating and culturing OC cells from patient ascites fluid and normal ovarian surface epithelial (OSE) cells from benign ovarian tissue sections. These cells maintain an epithelial phenotype and can be manipulated experimentally for several passages before cellular senescence. An example using TGFb1 treatment of OC cells to examine signaling and target gene activation is presented.